Influence Of Molarity And Time Of Potassium Hydroxide Etching On Al-Rich AlGaN Layer - Yusuf, Yusnizam; Wee, Kie Tang; Taib, Muhamad Ikram Md; Zainal, Norzaini (2020)
This work will describe the influence of molarity and time of potassium hydroxide etching on Al-rich AlGaN layer. With potassium hydroxide (KOH) molarity of 5 mol/L, no significant change on the pores formation was observed for 5 and 10 minutes of etching. Nonetheless, there was a possibilty that some of the Ga atoms were eliminated for 10 minutes of etching, resulting in co-existance of AlGaN material with higher Al content. Similar behaviour was also witnessed in the case for 10 mol/L of KOH with 5 and 10 minutes of etching. Nonetheless, well-defined hexagonal patterns were only formed when the etching was conducted using 10 mol/L of KOH for 10 minutes. Such patterns have the potential to increase light extraction efficiency of UV LEDs.